PERAN KOMITE SEKOLAH DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU AL-FITYAN GOWA - Ahmad Yani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This study aimed at discovering the description of the roles of school committee as advisory agency, supporting, controlling, mediator, and examining the effectiveness on the implementation of the roles of the committee at integrated Islamic Junior School (SMP IT) Al-Fityan Gowa. The result of the study revealed that (1) the roles of the school committe at SMP IT Al-Fityan Gowa based on the aspect of education qualification and the number of school committee was considered capable to run the roles based on four indicators as advisory agency, supporting, controlling, mediator. However, the fact was different with the reality which revealed that the school committee was categorized as minim to due to several factors, among others were: a) lack of socialization as the roles and functions of school committee to parents of refresentative of parents, society and stakeholder, b) the committee was yet supportet by other organization as AD/ART and office space, and c) the committee was mostly busy with other activities in other place which gave contribution on the implementation of the roles of the committee; (2) the effectiveness of the rolesof the committee based on the indicators of the implementation of the roles of committee was on the stage of parcitipated in providing consideration in terms of giving feedback and ratification on RAPBS, and RKS/RPS as well as providing financial support of BPP Monthly. As is role as a controller, the comite merely monitor the implementation of the school program and the result of the learning; whereas, its roles as a mediator ws merely conducted when it related to the mediation between the parent and the school.